2014
DOI: 10.3329/bmrcb.v40i1.20323
|View full text |Cite
|
Sign up to set email alerts
|

Cadaver study of the volume of the ovary in Bangladeshi women

Abstract: Reproductive age, ovarian reserve and reproductive capability may be determined from the volume of the ovary. A cross-sectional, descriptive study was done in the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…Average right-left differences have ranged from 0.5-1.6 mL (26,27,29,34,41), with one study (26) reporting an upper limit of agreement near 5.0 mL. Evidence that the right ovary is larger than the left ovary across the lifespan, from childhood (42) through the fourth decade (27,29) and postmortem (43), increases confidence in our findings. Differences in blood supply between the two ovaries could offer a physiological basis for one being larger-albeit studies (26,34,41,44,45) using Doppler ultrasound technology have yielded conflicting data on right-left differences in vascular indices, independent of gravidity or parity.…”
Section: Discussionsupporting
confidence: 60%
“…Average right-left differences have ranged from 0.5-1.6 mL (26,27,29,34,41), with one study (26) reporting an upper limit of agreement near 5.0 mL. Evidence that the right ovary is larger than the left ovary across the lifespan, from childhood (42) through the fourth decade (27,29) and postmortem (43), increases confidence in our findings. Differences in blood supply between the two ovaries could offer a physiological basis for one being larger-albeit studies (26,34,41,44,45) using Doppler ultrasound technology have yielded conflicting data on right-left differences in vascular indices, independent of gravidity or parity.…”
Section: Discussionsupporting
confidence: 60%
“…When data are interpreted, it should also be kept in mind that ovarian volume and ovarian surface area are smaller during childhood and at the end of the reproductive phase, which means that the total number of follicles can only be deduced to a limited extent from the cortical FD. Thus, ovarian volume changes with age (Orsini et al, 1984;Cohen et al, 1993;Goldberg and McGahan, 2006;Perven et al, 2014;El Issaoui et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The maximum ovarian volume is reached in young adults (8-14 cm 3 ) and declines thereafter. In a cadaver study the average ovary size in females aged 14-45 years was determined as 5.95 ± 1.37 cm 3 (right ovary) and 4.24 ± 1.05 cm 3 (left ovary) (Perven et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Perven at al. conducted a post-mortem study of human ovaries in the specific ethnic group of Bangladeshi women and found that the weight of right ovaries was significantly greater, compared to the left side [ 30 ]. As expected, the ovarian weight was significantly lower in the subgroup of women aged over 45 years.…”
Section: Discussionmentioning
confidence: 99%